THE EFFECT OF COMPETITOR ADVERTISING, MOUTH TO MOUTH MARKETING AND PRICE PERCEPTIONS ON THE TRANSFER OF OTHER BRANDS TO TELKOMSEL ON STUDENTS OF STIKUBANK UNIVERSITY SEMARANG - Septi Setiyorini; Mulyo Budi Setiawan (Universitas Putera Batam, 2022)
This study aims to analyze the effect of competitor advertising, word of mouth marketing and price perception on switching other brands to Telkomsel. The data used is sourced from a questionnaire in the form of a google form link (primary data). The sampling method used non-probability sampling method. The results showed that competitors' advertisements had a positive effect on brand switching, while word of mouth marketing and price perception had no effect on brand switching. The higher the competitor's advertisements, the higher the switching of other brands to Telkomsel. This study resulted in 61.1% of brand switching variables can be explained by competitor advertising, word of mouth marketing and price perception, while 38.9% is influenced by other variables outside the study.